A novel thermal-tuning Fe-based amorphous alloy for automatically recycled methylene blue degradation. (5th January 2019) - Yang, Weiming; Wang, Qianqian; Li, Wenyu; Xue, Lin; Liu, Haishun; Zhou, Jing; Mo, Jinyong; Shen, Baolong
Abstract: The comprehensive utilization of the excellent magnetic properties and advanced catalytic ability of Fe-based amorphous alloys (FAAs) is reported for the first time. A novel Fe63 Cr5 Nb4 Y6 B22 (at%) amorphous alloy that has ferromagnetic to paramagnetic transition near room temperature and good catalytic performance for methylene blue degradation is successfully synthesized. The alloy is applicable for automatically recycled dye degradation with its thermal-tuning magnetic behavior. When an external dye wastewater is applied (high temperature), the FAAs are paramagnetic and disperse into water to participate in degradation. When the wastewater has been degraded and the temperature drops to room temperature, the FAAs change to ferromagnetic and the remediated water can be released. This alloy exhibits a low thermal activation energy barrier of 21.8 kJ/mol due to the reduced atomic bonding forces with Cr addition, and has excellent catalytic performance at high temperature (323–343 K) and in acidic solution (pH = 3). The excellent chemical properties are mainly attributed to the heterogeneous structure consisting of local Fe-rich and Fe-poor atomic clusters. The present findings not only provide a new, highly efficient and low cost commercial method for wastewater treatments, but also shed light on the comprehensive utilization of the magnetic and chemical properties of FAAs. Graphical abstract: Highlights: Fe63 Cr5 Nb4 Y6 B22 amorphous ribbon with good catalytic ability in Fenton-like reaction was synthesized. An automatically recycled dye degradation system was designed based on Fe63 Cr5 Nb4 Y6 B22 amorphous ribbons. The good catalytic property of Fe63 Cr5 Nb4 Y6 B22 amorphous ribbons are attributed to their local heterogeneous structures.